Pengalaman Pasien Ketika Terjadi Intoksikasi Obat Pada Pengguna Zat Adiktif Stimulant Yang Di Rawat Di Rumah Sakit Jiwa Arif Zainudin Surakarta - Rinenggo, Ani Galih; , Arum Pratiwi, S.Kp., M.Kes (2017)
Drugs not only consist of the narcotics and psychotropic, but also contain addictive substances. Addictive substances is substances or material that very influential out of ychoactive narcotics and can caused addiction and dependency if used in continous period, not only psychical addiction, but physco addiction and used intensity of addiction bstance is a frequency or how much that period of employing. The purposes of this research is to know about patient experience when intoxication of drugs on addictive stimulant patient. This research is a qualitative research type be using the phenomenological approach. The respondents in this research is 5 peoples. Sample technicque that using is a purposive sampling technic. Data collection procedure in this research is using depth interview techniques. Data analysis thad used is a thematic analysis. The result of this research produced 4 themes, that is factors of using drugs, type of drugs that abused, drugs intoxication, and the support while drugs intoxication experience. In this research, respondent said that when he had drugs ntoxication experience, he feel that queasy, feverish, diarhea, being rage, and the usage at least 2 years and the longest is 4 years.